2018
DOI: 10.1002/ccd.27705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prior stroke on long‐term outcomes of percutaneous coronary interventions in Chinese patients: A large single‐center study

Abstract: Objectives: To evaluate the effect of prior stroke on long-term outcomes in patients undergoing percutaneous coronary interventions (PCI).Background: Patients with coronary heart disease (CHD) and prior stroke history have more serious clinical and angiographic conditions, which make the choice of treatment strategy complex.Methods: A total of 10,724 consecutive patients who underwent PCI from January 2013 to December 2013 were enrolled. 2-Year clinical outcomes between patients with prior stroke (n = 1150) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…These thresholds, close to those of our current work, could be proposed as a reference limit beyond which we could consider ischemia testing in patients at high CV risk. In agreement with the literature, we found that CV risk factors, such as hypercholesterolemia, CV history and elevated creatinine level, were strong predictors of extensive CAD [ 27 , 28 , 29 ]. Given the potential therapeutic strategies targeting VC, further studies are thus needed to better understand the place of OPG as a biomarker in ASCVD [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…These thresholds, close to those of our current work, could be proposed as a reference limit beyond which we could consider ischemia testing in patients at high CV risk. In agreement with the literature, we found that CV risk factors, such as hypercholesterolemia, CV history and elevated creatinine level, were strong predictors of extensive CAD [ 27 , 28 , 29 ]. Given the potential therapeutic strategies targeting VC, further studies are thus needed to better understand the place of OPG as a biomarker in ASCVD [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, a large number of literatures have reported that acupuncture combined with rehabilitation training is effective when treating motor dysfunction and nerve injury after stroke [ 13 ]. However, due to the lack of standardized and unified operation flow between Chinese and western medicine rehabilitation treatment programs, there are many problems such as great differences in intervention measures, nonuniform setting of the control group, and insufficient research sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that patients with prior stroke usually suffered from more events and higher mortality ( 17 , 18 ). Others showed similar incidence of non-cerebrovascular adverse events between patients with or without prior stroke and that PCI was considered to be safe and effective for CHD patient with prior stroke ( 7 , 19 ).…”
Section: Discussionmentioning
confidence: 96%
“…Some studies found that patients with prior stroke usually suffered from more events and higher mortality (17,18). Others showed similar incidence of non-cerebrovascular adverse events between patients with or without prior stroke and that PCI was considered to be safe and effective for CHD patient with prior stroke (7,19). In this study, although in-hospital outcomes were similar between the two groups, the incidence of adverse cardiovascular and cerebrovascular events of patients with prior stroke was significantly higher during a long-term follow-up of 5 years.…”
Section: Worse Long-term Prognosis Of Patients With Prior Strokementioning
confidence: 99%
See 1 more Smart Citation